The Effect of Local Revenue and Special Autonomy Fund on Human Development Index with Capital Expenditure as Intervening Variable (Case Study: Districts/Cities in Papua Province) - Nanda, Rizky; Khusaini, Moh. (Wacana Journal of Social and Humanity Studies, 2024)
This study aims to determine the effect of Regional Original Revenue (PAD) and Special Autonomy Fund (DOK) on the Human Development Index (HDI) through Capital Expenditure as an intervening variable. The data used is secondary data on 29 districts/cities in Papua Province for five years (2017-2021). The research method used is Panel Data Regression with the help of the E-views 9 application. Hypothesis testing is done through the T-Test to determine the direct effect and the Cobel Test to determine the indirect effect through the intervening variable. The results showed that PAD had no direct influence on HDI, while DOK and BM had a significant negative influence. As for the indirect effect, PAD and DOK have a negative significant indirect effect on HDI through BM. Keywords: regional original revenue, special autonomy fund, capital expenditure, human development